Recurrent PET FDG Uptake after Sequential Chemotherapy and Radiation Therapy for DLBCL of the Tibia: A Case Report and Review of the Literature - Edward F. Miles; Luke Balsamo; David B. Turton; William Graf (Case Reports in Oncological Medicine)
The aim of this paper is to report on the challenges associated with identifying disease recurrence following combined modality therapy (CMT) for primary lymphoma of the tibia in which an intramedullary nail has been placed. A patient with primary bone lymphoma (PBL) was treated with CMT (chemotherapy and radiation therapy). After a complete response, he has been followed for eighteen months by physical exam and radiographic imaging. Despite persistent increased tracer accumulation at the original site, he has no proven recurrence. Literature review showed a small number of retrospective, single institution reviews detailing clinical experience and expected outcome in patients treated with PBL limited to one bony site of disease. PBL presents a treatment challenge, particularly when a weight-bearing long bone is diffusely involved and followup is complicated after placement of stabilizing hardware. Close coordination of the oncology team and diagnostic radiology is required to ensure optimal outcome.